Organizing for reliability : a guide for research and practice - Ramanujam, Rangaraj; Roberts, Karlene H. (High reliability and crisis management., 2018)
Increasingly, scholars view reliability--the ability to plan for and withstand disaster--as a social construction. However, there is a tendency to evoke this concept only in the face of catastrophes, such as the British Petroleum oil spill or the Space Shuttle Challenger explosion. This book frames reliability as a fundamental issue in the study of organizations--one that can also improve day-to-day operations. Bringing together a diverse cast of contributors, it considers how we can account for the ability of some organizations to maintain high reliability and what we can learn from them. The chapters distinguish reliability from related lines of inquiry; take stock of relevant research from different disciplinary perspectives; highlight implications for practice; and identify directions, questions, and priorities for future research. The first of its kind in over twenty years, this volume delivers a dynamic base of shared knowledge and an integrative research agenda at a time when organizational reliability has never been so important.